ISO 9001 Certification And Performance In Manufacturing Industries - Yeap, Hock Cheng (2004)
The trend of implementing the ISO 9000 quality system has grown quickly throughout the world, including in developed countries like US, UK as well as developing countries in South-East Asia. This research will study the impact of ISO 9001 certification on manufacturing Industries in Malaysia. It focuses on the effectiveness of ISO 9001 certification on market performance, operation performance and personnel performance as well as the market strategy as moderating factor.